Lichen Sclerosus Atrophicus with Vitiligo in Pediatrics - Juan Carlos Yanes Macías; Mery Rosa Betancourt Trujillo; Lino Arístides Sánchez Galván; Damarys Díaz Leonard; Tamara Sánchez Estrada; Hugo Almeida Leyva (Revista Finlay)
Background: lichen sclerosus is a chronic inflammatory dermatosis of the skin and semi-mucous membranes. It mainly affects the vulva and the perianal region, the extragenital location seen between 15 and 20 % of cases, is rare in childhood. Objective: to describe 8 pediatric patients with lichen sclerosus at the Paquito González Cueto Cienfuegos University Pediatric Hospital. Methods: a descriptive, retrospective study of 8 patients followed in the dermatology outpatient clinic of the Paquito González Cueto University Pediatric Hospital in Cienfuegos was carried out. The information was extracted from the medical records of the patients. Age expressed in years, sex, race, genital involvement, evolution time in years, associated symptoms, other associated diseases were taken into account: vitiligo, dermatomyositis, scleroderma, lupus erythematosus, type of lesions, morphea, koebner and treatment. Results: 8 cases were described, all in pediatric patients with a mean age of 8 years and an evolution of 3.1 years, predominantly female, 37.5 % of the series had extragenital lesions and vitiligo 62.5 %, there were diagnostic delay in a patient. Conclusions: lichen sclerosus is a pathology that affects the quality of life of patients, its possible sexual and urinary repercussions and its potential risk of epinocellular carcinoma, for which it is necessary to make a timely diagnosis.